Making the business case for an addiction medicine consult service: a qualitative analysis - Kelsey C. Priest; Dennis McCarty (BMC, 2019)
Abstract Background As the drug poisoning crisis worsens in North America and opioid use disorder (OUD)-related hospital admissions increase, policymakers and hospital administrators are beginning to recognize the important role of hospitals in the OUD care continuum. This study explores and describes how U.S. addiction medicine physicians created and presented business propositions to hospital administrators to support the development of addiction medicine consult (AMC) services. Methods Fifteen qualitative interviews were completed with board-certified or board-eligible addiction medicine physicians from 14 U.S. hospitals. The interviews occurred as part of a broader mixed methods study exploring hospital service delivery for patients admitted with OUD. Using a directed content analysis, the transcribed interviews were coded, analyzed, and final themes consolidated. Results Semi-structured interviews completed with addiction medicine physicians from established (n = 9) and developing (n = 5) AMC services at 14 U.S. hospitals explored how clinical champions persuaded hospital administrators to support AMC service development. Four elements were foundational to making the "business case": 1) describing the prevalence of substance use disorder (SUD) or OUD in the hospital; 2) identifying the negative financial impacts of not treating SUDs during hospitalization; 3) highlighting the ongoing care quality and treatment gap for hospitalized patients with SUDs; and 4) noting the success of other institutional AMC services. Study findings informed the creation of tools to support AMC service development: 1) an AMC service business case template, and 2) an AMC service design and operations resource list. Conclusions OUD-related hospital admissions are unlikely to abate. Hospital administrators should consider innovative care delivery mechanisms to improve care for persons with OUD. AMC services may be a promising delivery mechanism to achieve this aim. For clinical and administrative champions, understanding how to communicate the potential effectiveness of this intervention to hospital leaders is an essential first step to AMC service creation.